Trends and frontiers of RNA methylation in cancer over the past 10 years: a bibliometric and visual analysis - Liu, Bo-Na; Gao, Xiao-Li; Piao, Ying (Frontiers in Genetics, 2024)
Purpose: To highlight the trends and frontiers of RNA methylation in cancer over the past 10 years. Methods: Research publications on RNA methylation in cancer were retrieved from the Web of Science Core Collection database. VOSviewer, CiteSpace, and Bibliometrix were used to conduct bibliometric and visualization analysis of countries, institutions, authors, journals, and keywords relevant to this field. Results: From 2014 to 2023, research on RNA methylation in cancer has developed rapidly, with an overall increase in the number of publications and citations. China (4320 papers, 115056citations), Sun Yat Sen University (274 papers, 15698 citations), and Zhang, Wei (48 papers, 893 citations) are respectively the countries, institutions, and authors with the highest number of published papers and citations. Frontiers in Oncology (182 papers, 2524 citations) and Molecular Cancer (69 papers, 9224 citations) are the journals with the highest number of published papers and citations in this field, respectively. Co-occurrence analysis of keywords indicates that the research topics can be divided into five clusters: Cluster one: The Role of RNA Methylation in Tumor Heterogeneity, Therapeutic Response, and Prognosis; Cluster two: The Role of Noncoding RNA in RNA Methylation and Tumors; Cluster three: Potential Therapeutic Targets of RNA Methylation in Tumors; Cluster four: The role of RNA methylation in tumor progression and metastasis: A case study of hepatocellular carcinoma and gastric cancer; Cluster five: Regulation mechanisms of m6A methylation in leukemia cell differentiation and tumorigenesis. Conclusion: This is the first comprehensive study using bibliometrics to analyze the trends and frontiers of RNA methylation in cancer over the past 10 years, pointing out promising research directions for the future and providing valuable references for researchers in this field.